Organoids as a model to study the human endometrium. Issue 4 (29th November 2022) - Li, Jianlin; Lin, Leqian; Zhong, Jiangming; Li, Xintong; Lee, Cheuklun; Chiu, Philip C. N.
Abstract : The endometrium is composed of glandular and luminal epithelia supported by stromal connective tissue and multiple other cell types. It is a dynamic organ that undergoes physiological and functional alteration during the menstrual cycle. Organoids resemble the primary tissue of origin to recapitulate their corresponding biological and pathological characteristics. They are known for their ability to undergo extensive expansion while maintaining their genomic stability, facilitating their long-term storage and high-throughput screening. The development of the three-dimensional endometrial organoid system, which recapitulates the structural and functional characteristics of the endometrial glands, provides a powerful tool to study the normal endometrium and its related diseases. The Web of Science was searched for relevant literature using the keywords "endometrium", "endometrial gland", "organoid", and "culture model"; a total of 134 articles were selected. In this review, the characteristics, applications, and limitations of endometrial epithelial organoids are discussed.